Physics Formula Application Based On Mobile Android For Tenth Grade High School - Yunita, Ida, Endah Sudarmilah, S.T., M.Eng, Yusuf Sulistyo Nugroho, S.T., M.Eng (2013)
The aim of design and building Fisikandroid application is presenting an education application based on mobile android that contains physics formulas with more attractive material so it will easy to be understood by students. Trial respondent application is students of SMA N 2 Sukoharjo. The background of this research is a merger between two concepts there are technology and education. Android as an operating system is growing into the media presentation of the physics material which presented more interesting and accessible to students. To building the application using eclipse Helios, SDK, JDK and You Wave Android as main program and Adobe CS 6, Any Video Converter, CorelDraw X5 as support programs. Method of data collection in this research is questionnaire and comparison of pretest result. The end result of this research is an educational application based on mobile android that contains the physics formulas of class X, which presented more attractive and easy to be understood by students. It is proved from the questionnaire that 86.67% of respondents agreed if this application has elements of education, 96% of respondents stated this is an attractive application, 82.67% respondents agreed the information in this application is easy to understand, and 86.67% of students experienced increases in value after using this application which means that this application can improve students understanding of the material presented.